2009
DOI: 10.1016/j.biopsych.2008.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation Induces Acute Behavioral and Cognitive Changes and Accelerates Neurodegenerative Disease

Abstract: BackgroundChronic neurodegeneration results in microglial activation, but the contribution of inflammation to the progress of neurodegeneration remains unclear. We have shown that microglia express low levels of proinflammatory cytokines during chronic neurodegeneration but are “primed” to produce a more proinflammatory profile after systemic challenge with bacterial endotoxin (lipopolysaccharide [LPS]).MethodsHere, we investigated whether intraperitoneal (IP) challenge with LPS, to mimic systemic infection, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
366
2
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 521 publications
(392 citation statements)
references
References 52 publications
12
366
2
12
Order By: Relevance
“…3). Evidence has shown that microglia exposed to systemic inflammatory stimuli have increased reactivity, leading to accelerated neuronal death and progression of CNS disease [189][190][191]. It has been suggested that primed microglia contribute to the increased response to a second inflammatory stimulus [192].…”
Section: Modulatory Function Of Mononuclear Phagocytes In Comorbiditiesmentioning
confidence: 99%
“…3). Evidence has shown that microglia exposed to systemic inflammatory stimuli have increased reactivity, leading to accelerated neuronal death and progression of CNS disease [189][190][191]. It has been suggested that primed microglia contribute to the increased response to a second inflammatory stimulus [192].…”
Section: Modulatory Function Of Mononuclear Phagocytes In Comorbiditiesmentioning
confidence: 99%
“…For this reason, LPS are commonly employed to mimic bacterial infections in experimental animals. The systemic inflammation mediated by the LPS can trigger a set of cellular and molecular events that are able to initiate neuroinflammation to affect cognitive function (Arai et al 2001;Cunningham et al 2009;Sparkman et al 2006) and reduce adult neurogenesis (Fujioka and Akema 2010;Monje et al 2003). It has been well documented that pregnant animals have an increased sensitivity to LPS compared to non-pregnant ones (Faas et al 2003;Kunnen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…After the testing period, the remaining food in the cylinder was weighed and the mouse was returned to its collective cage. Burrowing is an ethological task highly sensitive to systemic inflammation (Cunningham et al 2009). …”
Section: Experimental Groups and Inoculation -mentioning
confidence: 99%